Trust, Monitoring and Cooperation in Mixed-Motive Negotiations: A Casual Examination of Competing Theories and a Comparison across Levels - FERRIN, Donald L. (Institutional Knowledge at Singapore Management University, 2000)
Intergroup negotiations, including manager/employee relations, joint ventures, and corporate budgeting processes among others, are an important element of organizational life. Social dilemma theory and transaction cost economics both recognize the simultaneous presence of competitive and cooperative motives in such situations, and recognize the importance of factors that might encourage cooperative (or discourage 'opportunistic') behavior. Two factors that have received a substantial amount of theoretical attention, but far less empirical attention, are trust and monitoring. Based on existing theory, we developed a number of hypotheses about how trust, monitoring and cooperative behavior are interrelated. In doing so, we noted numerous disagreements about the valence of hypothesized relationships and their direction of causality. Accordingly, to test the hypotheses we selected a laboratory setting to reduce extraneous sources of variance and permit greater confidence in inferences we were to draw about the direction of causality. Contrary to hypotheses, we found that neither trust nor monitoring resulted in consistent changes in cooperative behavior. Also contrary to hypotheses, we found that trust and monitoring were not negatively related to (i.e., substitutes for) each other. We did, however, find strong support for the hypotheses that increases in cooperative behavior resulted in increased trust and decreased monitoring. Our findings suggest that scholars and practitioners should consider whether 'control mechanisms' like trust and monitoring are outcomes rather than determinants of cooperative behavior. Such a consideration may lead to significant changes in the way organizations are understood and managed.